Former Yugoslav Republic of Macedonia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper on Former Yugoslav Republic (FYR) of Macedonia investigates the macroeconomic impact of remittances on long-run external sustainability and growth. The paper presents stylized facts pertaining to the characteristics of remittances in Macedonia, highlighting their countercyclicality and importance in sustaining the purchasing power of domestic agents. The paper reviews to help set up a theoretical framework for assessing their macroeconomic impact, highlighting the possible risk of 'Dutch disease' developments. The paper uses a Bayesian vector autoregression (BVAR) model to empirically investigate both hypotheses of countercyclicality and Dutch disease effects and puts forward a few policy options that may be explored to better harness remittances to support investment and long-term growth. The paper suggests that strong political engagement in support of diaspora projects is a key point. The mobilization of diaspora savings for private and public investment would maximize the long-term benefits of remittances.